Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus (PHAGOCYTIC RESPONSE OF SWINE POLYMORPH LEUCOCYTES (IN VITRO) TO STREPTOCCOCUS EQUI SUBSP. ZOOEPIDEMICUS) - Iwan Harjono Utama; Aisjah Girindra; Fachriyan Hasmi Pasaribu; I Wayan Teguh Wibawan; Endhie D. Setiawan; Gatut Ashadi; Aida Louise Tenden Rompis (Jurnal Veteriner, 2016)
Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus